628.DISTRIBUTION OF SOME RADIONUCLIDES IN CORN AND SOIL FROM DIFFERENT LOCATIONS IN THE SURROUNDING OF SKOPJE - Aleksandra, Angjeleska; Elizabeta, Dimitrieska-Stojkovic; Radmila, Crceva-Nikolovska; Zehra, Hajrulai-Musliu; Biljana, Stojanovska-Dimzoska; Slobodan, Bogoevski; Bosko, Boskovski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
Concentration of natural radionuclides in soil and plants are crucial parameters for defining the level of contamination of the environment. The samples for analysis were collected from the 14 localities of the surrounding of Skopje, of cultivated and uncultivated soil. The specific activity of radionuclides 232Th, 226Ra and 40K are determined by gamma spectrometry. The analysis results show that the mean value of 232Th specific activity in cultivated soil was 43.74 ± 4.99 Bq·kg–1, while in uncultivated soil it was 35.70 ± 5.65 Bq·kg–1. The 226Ra specific activity had a mean value of 34.09 ± 6.53 Bq·kg–1 and 28.30 ± 5.54 Bq·kg–1 in cultivated and uncultivated soil, respectively. The specific activity of 40К from all localities was higher than the one of 232Th and 226Ra, and in cultivated soil the mean value was 608.12 ± 70.43 Bq·kg–1, while in uncultivated soil it was 506.54 ± 59.96 Bq·kg–1. From the same locations corn samples were also collected for analysis. Concentration of natural radionuclides in corn is lower then referent values. From the results ttransfer factor (TF) of natural radionuclides from soil to corn was calculated.